Implementasi Teknologi Literasi Digital Al Quran Hadis Sebagai Media Pembelajaran Di STIT Ar-Raudlatul Hasanah Medan - Ahmad Faisal; Abdul Aziz Sebayang; Isryad Saifullah; Bintang Tarigan (Program Studi Pendidikan Agama Islam, 2024)
This research aims to determine the basic knowledge and learning strategies for Al-Quran Hadith digital literacy technology among STIT Ar-Raudlatul Hasanah Medan students. This research was conducted using interviews and in-depth observation. The theory applied is the term digital literacy learning of the Koran Hadith. This research uses a qualitative method with a descriptive approach sourced from primary and secondary data. Primary data sources were obtained from student interviews. Meanwhile, secondary data comes from literacy activities held at STIT Ar-Raudlatul Hasanah. From the research results, it can be concluded that students' basic knowledge in digital literacy of the Koran Hadith is still inadequate. Meanwhile, the strategy applied to deepen digital literacy learning of the Koran Hadith is by conducting literacy learning training or workshops. The results of the implementation of digital literacy can be seen from the level of students' ability to master digital media technology, such as the al-Maktabah asy-Syamela program, HadisSoft, Al-Quran Madinah, QuranInMsWord and Adobe Reader relevant for STIT Ar-Raudlatul Hasanah Medan students.